Bamboo Fiber Composites Processing, Properties and Applications - Jawaid, Mohammad; Mavinkere Rangappa, Sanjay; Siengchin, Suchart (Composites Science and Technology, 2021)
This book summarizes many of the recent developments in the area of bamboo composites with emphasis on new challenges for the synthesis characterization, properties of bamboo composites and practical applications. The book provides an update of all the important areas of (synthesis, processing, properties and application) bamboo fibers and its composites in a comprehensive manner. The chapters contributed by leading researchers from industry, academy, government and private research institutions across the globe benefit academics, researchers, scientists, engineers and students in the field of natural fiber composites